HUBUNGAN BEBAN KERJA PERAWAT DENGAN PELAKSANAAN DISCHARGE PLANNING DI UNIT PELAKSANA TEKNIS DAERAH RUMAH SAKIT JIWA PROVINSI BALI - Wisnawa, Dewa Gede Ari; Rahajeng, Indah Mei; Darma Yanti, Ni Putu Emy (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022, 2022)
Nowadays, there was increase of household members with schizophrenia in Indonesia. The increase of mental disorders prevalence in Indonesia, especially Bali Province, has potential impact on increasing psychiatric nurses’ workload. The increasing of workload can affect psychiatric nurses’ productivity on their duties, one of them is implementing discharge planning. This study aimed to determine relationship between nurses’ workload and discharge planning implementation at Mental Hospital in Bali Province. This study was a quantitative study with correlative analytical study design. This study used stratified random sampling technique with total of respondent were 150 nurses. The results showed most respondents experienced heavy workload (52%) and carried out discharge planning well (84%). The results of the Spearman Rank test obtained p - value = 0,000 (p < 0,05) with r = 303, which means there was a weak positive relationship between nurse’s workload with discharge planning implementation at Mental Hospital in Bali Province.